If it's not what You are looking for type in the equation solver your own equation and let us solve it.
56=14g
We move all terms to the left:
56-(14g)=0
We move all terms containing g to the left, all other terms to the right
-14g=-56
g=-56/-14
g=+4
| 30=-3y+6(y+3) | | 7p2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 7p^2–2=0 | | 3(-2+6p)=3p-6 | | 3(-2+6p)=3p-6 | | 3(-2+6p)=3p-6 | | (8x)^2=8x^2 | | 7x−8=5x−16 | | 25=45-x | | 9(2m-)=18m-81 | | 7-2y/2-2/5(2-y)=1/1/4 | | 4u-8+2(2u+4)=-6(u+3) | | `8+4x=-10+x | | 4u-8+2(2u+4)=-6(u+3) | | -6+2v=2 | | 4(u+4)=-6u-24 | | 8x(X-2)=96 | | t+58=75 | | Y+6=3(x+1) | | Y+6=3(x+1) | | 3/2x+4=37 | | -(18+4x)=26 | | 3z/7-9=5 | | x*x=250 | | 2x+30=1.50x+12=3 | | (x*2)*(x/5)=250 | | -12=-3yy= | | -12=-3yy= | | (18-3x)-(4+2)=10 |